2019
DOI: 10.1186/s12910-018-0340-z
|View full text |Cite
|
Sign up to set email alerts
|

Does written informed consent adequately inform surgical patients? A cross sectional study

Abstract: BackgroundInformed consent (IC) is an essential step in helping patients be aware of consequences of their treatment decisions. With surgery, it is vitally important for patients to understand the risks and benefits of the procedure and decide accordingly. We explored whether a written IC form was provided to patients; whether they read and signed it; whether they communicated orally with the physician; whether these communications influenced patient decisions.MethodsAdult postsurgical patients in nine general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 30 publications
5
71
0
2
Order By: Relevance
“…In this sense, the use of shadowing helps to understand the experience in a real time context. Moreover, it is always useful to evaluate whether the tools and information methods used for giving information to patients are effective, and which is the best moment for each patient to receive all the information they need, by considering their ability to absorb the information in a stressful situation [4648].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the use of shadowing helps to understand the experience in a real time context. Moreover, it is always useful to evaluate whether the tools and information methods used for giving information to patients are effective, and which is the best moment for each patient to receive all the information they need, by considering their ability to absorb the information in a stressful situation [4648].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, five phrases with higher burst were selected for in-depth analysis: "Informed consent, " "Surgery, " "Depression, " "Older adult, " and "Patient-centered care." "Informed consent" is a dynamic process used to build mutual trust, in which the clinicians communicate with the patients to ensure that the patients know his or her own treatment decisions, and it usually includes oral communication and text material (22). A cross sectional study showed that age and level of education may influence the adequacy of written informed consent for surgical patients (22).…”
Section: Research Hotspots and Frontiersmentioning
confidence: 99%
“…"Informed consent" is a dynamic process used to build mutual trust, in which the clinicians communicate with the patients to ensure that the patients know his or her own treatment decisions, and it usually includes oral communication and text material (22). A cross sectional study showed that age and level of education may influence the adequacy of written informed consent for surgical patients (22). Especially, a recent article (23) highlighted that the concept of traditional "Informed Consent" is evolving to match the requirements of the relatively new era of SDM.…”
Section: Research Hotspots and Frontiersmentioning
confidence: 99%
“…However, it is the form’s role as a record of the consent conversation that is perhaps under-researched. Few authors have examined this area, although some have included the consent conversation as an adjunct to research focused on the form itself, 9 while others have examined the respective roles of the form and the conversation with a view to improving the consent process. 10 …”
Section: Introductionmentioning
confidence: 99%